POTENSI PERFOMA PENDINGINAN MODUL TERMOELEKTRIK TEC1-12710 DAN TEC1-12715 SR DENGAN METODA OPTIMASI PENDINGINAN SISI PANAS MENGGUNAKAN BEBERAPA JENIS PENUKAR KALOR - Kurniasetiawati, Annisa Syafitri; Prasetyo, Bowo Yuli (AUSTENIT, 2024)
Thermoelectric module is a mature technology that have been used in cooling applications such as special product storage cabins and cooling electronic products. Compared to the conventional technology (vapor compression systems), thermoelectric modules offer many advantages. However, in terms of cooling performance, particularly for large cooling capacities (>100Watt), thermoelectric modules still lag the conventional technology. One method that can be used to improve the cooling performance of thermoelectric modules is cooling the hot side of the module using a heat exchanger. In this study, experiments will be carried out on the TEC1-12710 and TEC1-12715 SR modules which alternately combined with five types of heat exchangers on the hot side of the module, connected by thermal paste. The types of heat exchangers used are Square HE, Round HE, Two-Pipe HE, Four-Pipe HE, and Liquid-Cooler HE. The experiments are carried out with operating voltage variations of 12V, 9V and 6V for each thermoelectric module. The data analysis results found that the best COP value was obtained by the TEC1-12715 SR thermoelectric module with the Round type Heat Exchanger of 0.767 at a voltage of 6V. For the TEC1-12710 thermoelectric module, the highest COP value was also obtained when the module was paired with a Round type Heat Exchanger at a voltage of 6V, with a value of 0.620. Additionally, the highest heat absorption value for both thermoelectric modules was obtained at a voltage of 12V using the Round type heat exchanger, namely 19.61 Watts (TEC1-12710) and 26.98 Watts (TEC1-12715 SR), respectively.